2014
DOI: 10.1371/journal.pone.0105226
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in SPARC and Coal Workers' Pneumoconiosis Risk in a Chinese Population

Abstract: BackgroundThe SPARC is a crucial matricellular protein and may influence the course of various diseases like tumor metastasis and fibrosis. In the present study, we investigated the association between the potential functional polymorphisms in SPARC and coal workers' pneumoconiosis (CWP) risk in a Chinese population.MethodsFive potentially functional polymorphisms (rs1059279, rs1059829, rs1053411, rs2304052 and rs4958281) in SPARC were genotyped and analyzed in a case-control study including 697 CWP cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The genetic variations contribute to the individual susceptibility and the severity of CWP. Our previous research has shown that three functional SPARC SNPs (rs1059279, rs1059829, and rs1053411) are associated with the increased risk of CWP [ 22 ]. Additionally, rs522616 in the promoter region of the matrix metalloproteinase 3 (MMP3) gene is correlated with a decreased risk of CWP, especially among the subgroup of no smokers and patients with Stage I [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variations contribute to the individual susceptibility and the severity of CWP. Our previous research has shown that three functional SPARC SNPs (rs1059279, rs1059829, and rs1053411) are associated with the increased risk of CWP [ 22 ]. Additionally, rs522616 in the promoter region of the matrix metalloproteinase 3 (MMP3) gene is correlated with a decreased risk of CWP, especially among the subgroup of no smokers and patients with Stage I [ 23 ].…”
Section: Discussionmentioning
confidence: 99%